A Bibliometric and Thematic Analysis of Key Performance Indicators in Agricultural Supply Chains - Sindhwaani, Deeksha; Mohapatra, Dipti Ranjan; Goyal, Anil Kumar (Prabandhan: Indian Journal of Management, 2026)
Purpose : This study sought to define and organize key performance indicators (KPIs) pertinent to agricultural supply chain management (SCM) and to investigate their interrelationships for the assessment of supply chain performance within the agricultural sector. Methodology : A comprehensive analysis of literature was conducted using the Scopus database, covering the period from 2014 to 2023. We used predefined inclusion and exclusion criteria to screen relevant papers and conducted thematic and keyword co-occurrence analyses to derive KPIs. We consulted experts to ensure that the shortlisted KPIs were applicable to agricultural supply chains. Findings : The research delineated a thorough KPI system organized into financial, operational, quality, and environmental performance categories. The results showed that metrics of financial stability, operational efficiency, and sustainability were critical for assessing the performance of the agricultural supply chain. The framework also showed how these characteristics were interconnected, supporting a more holistic evaluation of performance. Practical Implications : The proposed KPI framework provided managers with a formal framework for monitoring, comparing, and improving supply chain performance across different phases of agricultural operations. Originality : This research developed a sector-specific KPI framework for agricultural supply chains, grounded in bibliometric and expert-validated evidence. This feature differed from other studies that provided general indicators of supply chain performance.